THU0007 INDIVIDUALIZED PATHWAY ANALYSIS FROM WHOLE BLOOD TRANSCRIPTOMIC IN SSC PATIENTS DEMONSTRATES UNIQUE CORRELATIONS WITH DISEASE SEVERITY. (2nd June 2020) - Bellocchi, C.; Rossato, M.; Barturen, G.; Segatto, G.; Vigone, B.; Makowska, Z.; Buttgereit, A.; Kerick, M.; Alarcon-Riquelme, M.; Martin Ibanez, J.; Beretta, L.
Abstract : Background: Genome-wide gene expression profiles and pathways analysis may help to discover deregulated processes underlying the pathogenesis of complex diseases or their phenotypic expression. Little or nothing is currently known about pathways associated with disease severity and damage in SSc. Objectives: To perform a whole blood transcriptome analysis and to characterize the individualized functional pathways associated with disease severity scores in SSc patients via a discovery and replication strategy. Methods: Whole blood samples were collected in RNA stabilizers from a discovery and a replication cohort of 67 and 34 patients, respectively. RNAseq data were generated by Illumina sequencing in two independent experiments pathways analysis was conducted according to the Functional Analysis of Individual Microarray Expression (FAIME) protocol (1). FAIME scores from Reactome pathways were correlated with the Scleroderma Clinical Trial Consortium Damage Index (SCTC-DI) total scores or with each of its two components (mortality and morbidity) as calculated from regression coefficient previously published (2). A non-parametric partial correlation analysis correcting the results for the use of steroids, immunosuppressants and disease duration was performed. Results independently associated with damage in both cohorts at the 0.1 level after 1000-fold permutation-testing were considered as significant and replicated. Results: A total of 1116 pathways were analyzed. None of them was associated in both cohorts with the total SCTC-DI; similarly, no association was found with the SCTC mortality component. On the contrary, 26 pathways showed an independent and replicated association with the SCTC morbidity component, including platelet degranulation, the transcriptional activity of SMAD2/SMAD3, Toll Like Receptor 2 (TLR2) cascade and related intracellular signaling events involving MyD88, IRAK and NF-kB, and the deregulation of selected transcription factors (TFAP2, E2F6). Conclusion: Selected molecular events involving the innate immune system, signaling and platelet metabolism are associated with the morbidity component of the SCTC-DI in SSc patients, reflecting an irreversible loss of function in several organs and apparatus. The sensitivity of these associations to individual change in accrual damage is to be determined. References: [1]PMID: 22291585; (2) PMID: 30928903 Acknowledgments: This work was partially supported by EU/EFPIA/Innovative Medicines Initiative Joint Undertaking PRECISESADS grant No. 115565 Disclosure of Interests: Chiara Bellocchi: None declared, Marzia Rossato: None declared, Guillermo Barturen: None declared, Giulia Segatto: None declared, Barbara Vigone: None declared, Zuzanna Makowska Employee of: Bayer AG, Anne buttgereit Employee of: Bayer AG, Martin Kerick: None declared, Marta Alarcon-Riquelme: None declared, Javier Martin Ibanez: None declared, Lorenzo Beretta Grant/research support from: Pfizer